2013
DOI: 10.1126/science.1237908
|View full text |Cite
|
Sign up to set email alerts
|

Structure of Parkin Reveals Mechanisms for Ubiquitin Ligase Activation

Abstract: Mutations in the PARK2 (parkin) gene are responsible for an autosomal recessive form of Parkinson's disease. The parkin protein is a RING-in-between-RING E3 ubiquitin ligase that exhibits low basal activity. We describe the crystal structure of full-length rat parkin. The structure shows parkin in an autoinhibited state and provides insight into how it is activated. RING0 occludes the ubiquitin acceptor site Cys(431) in RING2, whereas a repressor element of parkin binds RING1 and blocks its E2-binding site. Mu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

29
643
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 470 publications
(686 citation statements)
references
References 40 publications
29
643
1
Order By: Relevance
“…Three‐dimensional structures show that most of the affected residues form a cluster anchored by W403 that follows the short helix in the tether region and is essential for packing the tether against the RING0/RING1/RING2(Rcat) core (Fig 3A and B). In the absence of Ub or Ubl phosphorylation by PINK1, a W403A parkin variant dramatically increases ubiquitination activity (Trempe et al , 2013), likely a result of a structural rearrangement near W403 and exposure of the subsequent catalytic C431 in the RING2(Rcat) domain. Therefore, we hypothesized that UbcH7‐Ub binding to R0RBR:pUb might cause a similar rearrangement near the RING0/RING1/RING2(Rcat) core in the wild‐type protein as in the W403A substituted version (R0RBR W403A ).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Three‐dimensional structures show that most of the affected residues form a cluster anchored by W403 that follows the short helix in the tether region and is essential for packing the tether against the RING0/RING1/RING2(Rcat) core (Fig 3A and B). In the absence of Ub or Ubl phosphorylation by PINK1, a W403A parkin variant dramatically increases ubiquitination activity (Trempe et al , 2013), likely a result of a structural rearrangement near W403 and exposure of the subsequent catalytic C431 in the RING2(Rcat) domain. Therefore, we hypothesized that UbcH7‐Ub binding to R0RBR:pUb might cause a similar rearrangement near the RING0/RING1/RING2(Rcat) core in the wild‐type protein as in the W403A substituted version (R0RBR W403A ).…”
Section: Resultsmentioning
confidence: 99%
“…What is less clear is how parkin positions the E2~Ub conjugate to enable transfer of the Ub molecule to the RING2(Rcat) domain as a necessary step for catalysis. Current crystal structures of parkin show the proposed E2 binding site on the RING1 domain is > 50 Å from the catalytic site (C431) in the RING2(Rcat) domain suggesting a significant conformational rearrangement is needed (Riley et al , 2013; Trempe et al , 2013; Wauer & Komander, 2013; Kumar et al , 2015, 2017; Sauvé et al , 2015; Wauer et al , 2015). A similar dilemma arises from recent structures of HHARI in complex with UbcH7‐Ub that show the ubiquitin molecule is 47–53 Å from the catalytic site (Dove et al , 2017; Yuan et al , 2017).…”
Section: Introductionmentioning
confidence: 99%
“…6 mutation of the protein to disrupt formation of this conformation increased the activity of the ligase and its recruitment to mitochondria compared with no mutation. Fon told SciBX, "We are now looking for small molecules that disrupt this autoinhibitory interaction.…”
Section: All In the Familymentioning
confidence: 99%
“…The kinase activity of PINK1 is required for the translocation and activation of Parkin, a cytosolic E3 ubiquitin ligase that acts as a quality control guard by ubiquitinating proteins of the outer mitochondrial membrane to trigger selective autophagy of the damaged mitochondria, a process termed mitophagy ( Figure 1). Recent structures of Parkin revealed that the protein adopts an inactive conformation under basal conditions and needs to undergo a structural rearrangement to become active [2][3][4][5]. Mutation of residues involved in maintaining the inactive conformation (e.g., a tryptophan in the repressor element of Parkin, or REP) led to an increase in Parkin activity [2].…”
mentioning
confidence: 99%
“…Recent structures of Parkin revealed that the protein adopts an inactive conformation under basal conditions and needs to undergo a structural rearrangement to become active [2][3][4][5]. Mutation of residues involved in maintaining the inactive conformation (e.g., a tryptophan in the repressor element of Parkin, or REP) led to an increase in Parkin activity [2].…”
mentioning
confidence: 99%